State Characteristics and the Location of Foreign Direct Investment within the United States - Coughlin, Cletus C.; Terza, Joseph V.; Arromdee, Vachira (The Review of Economics and Statistics, 1991)
Cletus C. Coughlin, Joseph V. Terza, Vachira Arromdee, State Characteristics and the Location of Foreign Direct Investment within the United States, The Review of Economics and Statistics, Vol. 73, No. 4 (Nov., 1991), pp. 675-683